PENGEMBANGAN PENDIDIKAN AGAMA BERBASIS BUDAYA SEKOLAH DALAM MENGATASI PROBLEMATIKA PENDIDIKAN AGAMA - Khoiri, Miftakul (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2020)
Religious education plays an important role in carrying out development in particular in shaping and printing young people who are moral and quality. Religious education serves to make people who believe in obedience to the commands and prohibitions of their religion and apply to everyday life. But what happens in the world of education today does not say so, the classic problems that occur to date are still not resolved properly and continue to be a continuing problem. Such as the problem of using time allocation that is too narrow which is used in the learning process, namely the religious learning elementary school is only 3 hours face to face and junior high school, high school / vocational school is only 2 hours face to face and every hour is 45 minutes not 60 minutes, of course this is very poor considering the purpose religious education is so great for the development and development of the nation. Not to mention if in one school there are various religions. The development of religious education by applying school culture that applies the principles of development through learning activities, giving values and parameters for achieving this school can be an alternative solution regarding the existing problems.